Livestock grazing impacts components of the breeding productivity of a common upland insectivorous passerine: Results from a long‐term experiment. Issue 8 (31st May 2020) - Malm, Lisa E.; Pearce‐Higgins, James W.; Littlewood, Nick A.; Karley, Alison J.; Karaszewska, Ewa; Jaques, Robert; Pakeman, Robin J.; Redpath, Stephen M.; Evans, Darren M.
Abstract: The intensity of pastoral management in areas of High Nature Value farming is declining in some regions of Europe but increasing in others. This affects open habitats of conservation concern, such as the British uplands, where bird species that benefit from low‐intensity grazing may be most sensitive to such polarization. While experimental manipulations of livestock grazing intensities have improved our understanding of upland breeding bird responses in the short term, none have examined the long‐term impacts of altered management on reproductive success. Using a replicated landscape‐scale experiment that started in 2003, we investigated the effects of four grazing treatments (intensive sheep; low‐intensity sheep; low‐intensity mixed sheep and cattle; and no grazing) on the breeding productivity of meadow pipits Anthus pratensis, the most common upland passerine. Surveys were carried out systematically during early (2003 and 2004) and late (2015 and 2016) sampling periods of the experiment to compare the short‐ and long‐term effects of grazing treatments on breeding density and productivity of pipits specifically, but also on the overall bird community. Pipit breeding density was lowest under low‐intensity sheep grazing while the highest egg‐stage nest survival was observed in the same treatment, although no significant treatment effects were detected on overall nest survival or fledgling output. There were no significant differences in treatment effects between the sampling periods on any breeding variable, but overall nest survival was lower in the later sampling period across all treatments. Breeding bird species richness differed between treatments in the later sampling period, with highest species richness in the ungrazed treatment. Synthesis and applications . Livestock grazing management can have different outcomes for different upland birds. Our results showed that, with time, meadow pipit breeding productivity tended to be higher when sheep grazing intensity was reduced and/or mixed with cattle, and lower when livestock were removed, but not significantly so. Removal of grazing, however, can significantly increase bird species richness. The long‐term experiment showed an overall decline in fledglings regardless of grazing treatments, potentially a result of increased predator numbers harboured by nearby developing woodland, highlighting the importance of considering wider landscape processes in grazing management decisions. Abstract : Livestock grazing management can have different outcomes for different upland birds. Our results showed that, with time, meadow pipit breeding productivity tended to be higher when sheep grazing intensity was reduced and/or mixed with cattle, and lower when livestock were removed, but not significantly so. Removal of grazing, however, can significantly increase bird species richness. The long‐term experiment showed an overall decline in fledglings regardless of grazing treatments, potentially a result of increased predator numbers harboured by nearby developing woodland, highlighting the importance of considering wider landscape processes in grazing management decisions.